NLRX1 Deficiency Alters the Gut Microbiome and Is Further Exacerbated by Adherence to a Gluten-Free Diet - Morrison, Holly A.; Liu, Yang; Eden, Kristin; Nagai-Singer, Margaret A.; Wade, Paul A.; Allen, Irving C. (Frontiers in Immunology, 2022)
Patients with gluten sensitivities present with dysbiosis of the gut microbiome that is further exacerbated by a strict adherence to a gluten-free diet (GFD). A subtype of patients genetically susceptible to gluten sensitivities are Celiac Disease (CeD) patients, who are carriers of the HLA DR3/DQ2 or HLA DR4/DQ8 haplotypes. Although 85-95% of all CeD patients carry HLA DQ2, up to 25-50% of the world population carry this haplotype with only a minority developing CeD. This suggests that CeD and other gluten sensitivities are mediated by factors beyond genetics. The contribution of innate immune system signaling has been generally understudied in the context of gluten sensitivities. Thus, here we examined the role of NOD-like receptors (NLRs), a subtype of pattern recognition receptors, in maintaining the composition of the gut microbiome in animals maintained on a GFD. Human transcriptomics data revealed significant increases in the gene expression of multiple NLR family members, across functional groups, in patients with active CeD compared to control specimens. However, NLRX1 was uniquely down-regulated during active disease. NLRX1 is a negative regulatory NLR that functions to suppress inflammatory signaling and has been postulate to prevent inflammation-induced dysbiosis. Using Nlrx1-/- mice maintained on either a normal or gluten-free diet, we show that loss of NLRX1 alters the microbiome composition, and a distinctive shift further ensues following adherence to a GFD, including a reciprocal loss of beneficial microbes and increase in opportunistic bacterial populations. Finally, we evaluated the functional impact of an altered gut microbiome by assessing short- and medium-chain fatty acid production. These studies revealed significant differences in a selection of metabolic markers that when paired with 16S rRNA sequencing data could reflect an overall imbalance and loss of immune system homeostasis in the gastrointestinal system.